F-region drift current and magnetic perturbation distribution by the X-wave heating ionosphere - Y. Li; Y. Li; H. Li; J. Wu; J. Wu; X. Lv; X. Lv; X. Lv; C. Yuan; C. Yuan; C. Yuan; C. Li; et al. (Annales Geophysicae, 2023)
We present a theoretical and numerical study of the drift current and magnetic perturbation model in the ionosphere by incorporating the ohmic heating model and the magnetohydrodynamic (MHD) momentum equation. Based on these equations, the ionospheric electron temperature and drift current are investigated. The results indicate that the maximum change in electron temperature ΔTe is about 570 K, and the ratio is ΔTe/Te<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="36pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="89ed94e2716d485411679d449e71b6b0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-41-541-2023-ie00001.svg" width="36pt" height="14pt" src="angeo-41-541-2023-ie00001.png"/></svg:svg> ∼ 48 %. The maximum drift current density is 8×10-10<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="fd33264e50dc5150a72b5fe5cda2ffba"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-41-541-2023-ie00002.svg" width="46pt" height="14pt" src="angeo-41-541-2023-ie00002.png"/></svg:svg> A m−2, and its surface integral is 5.76 A. Diamagnetic drift current is the main form of current. The low collision frequency between charged particles and neutral particles has little effect on the current, and the collision frequency of electrons and ions is independent of the drift current. The current density profile is a flow ring. We present the effective conductivity as a function of the angle between the geomagnetic field and the radio wave; the model explains why the radiation efficiency was strongest when the X wave is heating along the magnetic dip angle, as reported in recent observations by Kotik et al. (2013). We calculate the magnetic field variation in the heating region based on the MHD theory: the results show that the maximum magnetic field perturbation in the heating area is 48 pT.